Expert examples and prompted reflection in learning with self‐generated concept maps. (5th November 2021) - Eshuis, Elise H.; ter Vrugte, Judith; Anjewierden, Anjo; de Jong, Ton
Abstract: Background: Creating concept maps can help students overcome challenges of accurate knowledge monitoring and thus foster learning. However, students' knowledge often contains gaps and misconceptions, even after concept map creation. Theoretically, students could benefit from additional support, but it is unclear whether this might also be the case for (more practical‐oriented) secondary vocational students. Objectives: This study investigated whether the effectiveness of concept maps for learning could be improved by providing students with expert examples and reflection prompts in addition to their self‐generated concept maps. Methods: First‐year secondary vocational students ( N  = 91, M age  = 17.3 years) participated in this study, which utilized a pretest‐intervention‐posttest design. Regarding the intervention, students worked in two successive online learning environments, in which they had to present their knowledge in concept maps. After creation, students' concept maps were, depending on condition, supplemented with (1) an expert example with comparative feedback (a combined concept map) and related reflection prompts, (2) the combined concept map only, or (3) no combined concept map and no prompts. Results and Conclusions: Analyses based on students' domain knowledge demonstrate that students significantly increased their knowledge in all conditions. Data indicate that there was no significant difference in knowledge gain between conditions. Further analysis showed that students in the experimental conditions demonstrated higher learning gains if they consulted the combined concept map more often than their peers. Implications: Access to an example in addition to students' self‐generated concept maps seems promising in fostering their knowledge acquisition. However, secondary vocational students might need additional ways of support to guarantee higher learning gains. Avenues to increase the effectiveness of support are discussed. Lay Description: What is currently known about the subject matter: Creating a concept map can be an effective means to promote student learning by facilitating their knowledge monitoring. Students' knowledge often contains gaps and misconceptions, even after concept map creation. There is evidence that feedback is needed to realize an effect on students' learning. What is the paper adding to this: Innovative implementation of concept map feedback in a self‐directed online learning environment. Exploration of the added value of support to process concept map feedback. Focus on a generally overlooked and unique target group: secondary vocational students. What are the implications of study findings for practitioners: The adopted unique implementation of concept map feedback seems promising for increasing students' learning. When designing support for secondary vocational students it is necessary to take the unique characteristics of these learners into account.